Dynamic positioning of Rpc34 winged helix in RNA polymerase III elongation complex for its stability with implications for reinitiation - Jheng-Syong Wu; Yu-Chun Lin; Yi-Yu Wei; Hsin-Hung Lin; Yang-Chih Liu; Jen-Wei Chang; I-Ping Tu; Hung-Ta Chen; Wei-Hau Chang (Proceedings of the National Academy of Sciences, 2026)
RNA polymerase III (Pol III) is specialized for the high-throughput synthesis of short RNAs, a capability linked to its unique TFIIE- and TFIIF-like subcomplexes that are stably associated through different stages of transcription. To date, the role of a winged helix domain (WH2) of Rpc34 subunit in the TFIIE-like subcomplex during elongation has remained a conundrum because its density is consistently absent in cryo-EM structures of Pol III elongation complexes (ECs), suggesting its high conformational mobility. In this study, we employed single-molecule Förster resonance energy transfer (smFRET) and nano-positioning triangulation to characterize the dynamics and determine the position of the Rpc34-WH2 domain within transcription-competent but nontranslocating Pol III ECs. To achieve the required site-specific labeling, we developed a chemical biology framework that utilizes azido-carrying unnatural amino acid incorporation and a thiol-capping strategy to eliminate off-target alkyne-thiol cross-reactivity. With the acceptor at Rpc34-WH2 and the donor at a defined position on the DNA template as the reference point, our smFRET results reveal that Rpc34-WH2 dynamically transitions among three discrete states, corresponding to preferred positional sites in downstream, middle, and upstream regions across the DNA-binding cleft. One of these sites coincides with Rpc34-WH2’s position in the preinitiation complex, indicating positional similarity across transcriptional states. Together with prior Pol I and Pol II studies, these findings establish Rpc34-WH2 as a mobile regulatory element that engages the Pol III EC through transient, weak interactions. Additionally, the bio-orthogonal labeling strategy presented here provides a robust, generalizable route for smFRET studies of large, multisubunit protein assemblies.